Effect of Nanotube Geometry on the Strength and Dispersion of CNT-Cement Composites. (27th July 2017) - Mohsen, Mohamed O.; Taha, Ramzi; Abu Taqa, Ala; Al-Nuaimi, Nasser; Al-Rub, Rashid Abu; Bani-Hani, Khaldoon A.
Abstract : This study investigated the effect of multiwalled carbon nanotubes' geometry on the dispersion and strength of cement composites. Mixes with CNTs contents ranging from 0.03 to 0.25% were prepared and tested using CNTs' diameters of 10–20, 20–30, and 30–50 nm and lengths of 0.5–2 and 10–30  μ m. The samples' microstructures were then examined using a scanning electron microscope. After that, Response Surface Methodologies techniques were implemented to determine the strength functions' response to the aspect ratio and weight fraction variables. The results showed that CNTs of smaller diameters and longer lengths resulted in the highest strength values in batches having CNT contents of up to 0.15%. At 0.25% CNTs, the results showed that those CNTs of shorter lengths attained higher strengths than those of longer ones. SEM images showed better dispersion properties at lower CNTs' contents regardless of their geometry. The analysis also indicated that short CNTs of 0.5–2  μ m length have better dispersion properties compared to long ones of 10–30  μ m length. The RSM model confirmed this finding. Furthermore, the model showed that the CNTs with the lowest aspect ratio of 83 and highest weight fraction of 0.25% provided the highest strength response among all batches.